การขยายพันธุ์ในหลอดทดลองและรูปแบบโครมาโทกราฟฟีของ กันภัยมหิดลที่ปลูกตามธรรมชาติ และแคลลัส - รวิกานต์ ระลึกฤๅเดช (จุฬาลงกรณ์มหาวิทยาลัย, 2012)
Tissue culture technique is one of advantageous methods for plant breeding. In addition, it can be used toeffectively yield active compound substituting for plant extract from natural resources. In the study, calluscultures of Afgekia mahidoliae B. L. Burtt & Chermsir (known as Kan Phai Mahidol), a rare tropical climber,were established to determine an appropriate composition of callus induction medium. Their chemical profileswere compared to those of naturally-grown plant. Calli were induced from leaves and nodes in Murashige andSkoog (MS) medium supplemented with 2, 4-dichlorophenoxy-acetic acid (2, 4-D) and 6-benzylaminopurine(BA). MS medium supplemented with 1.0 mg/L 2,4-D and 0.1 mg/L BA showed the highest callus inductionpercentage. The calli and naturally-grown leaves were extracted in ethanol and their chemical profiles wereanalyzed by Thin Layer Chromatography (TLC) using three mobile systems including hexane : ethyl acetate(7:3), ethyl acetate : dichloromethane (2:3), and dichloromethane : methanol (10:1). Chromatographic patternson TLC showed that chemical profiles of both extracts were different when detected under ultraviolet (UV)light at 254 and 365 nm. After sprayed with 10% sulfuric acid and detected under UV365, callus extract showedmoderate to high polarity of chemical compounds which were not observed in the naturally-grown leaf extract.